equação de 1° grau
a)
![4x - 11 = 2x + 2 4x - 11 = 2x + 2](https://tex.z-dn.net/?f=4x+-+11+%3D+2x+%2B+2)
b)
![4x - 7 = 8x - 2 4x - 7 = 8x - 2](https://tex.z-dn.net/?f=4x+-+7+%3D+8x+-+2)
c)
![9x + 9 + 3x = 15 9x + 9 + 3x = 15](https://tex.z-dn.net/?f=9x+%2B+9+%2B+3x+%3D+15)
d)
![5x - 3 + x = 2x + 9 5x - 3 + x = 2x + 9](https://tex.z-dn.net/?f=5x+-+3+%2B+x+%3D+2x+%2B+9)
responda passo a passo por favor
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
a) 4x - 11 = 2x + 2
4x - 2x = 2 + 11
2x = 13
x= 13/2
x= 6,5
b) 4x -7 = 8x - 2
2 - 7 = 8x - 4x
-5 = 4x
-5/4 = x
-1,25 = x
c) 9x + 9 + 3x = 15
9x + 3x = 15 - 9
12x = 6
x= 6/12
x = 0,5
d) 5x - 3 + x = 2x + 9
5x + x - 2x = 9 + 3
4x = 12
x = 12 / 4
x = 3
Perguntas interessantes
Geografia,
6 meses atrás
ENEM,
6 meses atrás
Matemática,
7 meses atrás
Biologia,
7 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás